SISTEM PELAYANAN DUKUNGAN ROLE ONLINE SYSTEM TICKETING RAHARJA (ROOSTER) DENGAN MENGGUNAKAN E-TICKET - Untung Rahardja; Nur Azizah; Santika Dewi (CCIT Journal, 2013)
The development of a more advanced age supports the need to provide different types of services that can be accessed in various ways easily, quickly, efficiently, whenever and wherever. Interactions that were once done physically (direct person to person contact) began to shift to electronic (communication through technology innovations) because relative electronic communications can be done efficiently, effectively, accurate, safe, comfortable, and quality. Therefore, the making of an application system support services and accurate highly recommended. With online methods based systems, system service support will be very easy to obtain. The ROOSTER is an application based support service system that is very practical. In this article describe the issues that arise as well as solving the problems examined. In addition there are three (3) characteristics and 5 (five) advantage of this application. In the implementation shown protoype view of the application ROOSTER. It can be concluded that the contribution of the system to maximize ROOSTER various forms of service, and can be used as media support service system that is valid for the entire academic community colleges and the general public.